On Optimal Estimate of the Block Orthogonal Greedy Algorithm for g-Frames. (23rd August 2021) - Poumai, Khole Timothy; Deep, Sunder; Kaushik, S. K.
Abstract: We obtain an optimal approximation of the block orthogonal greedy algorithm with regard to g-frames in Hilbert spaces and prove an optimal approximation result analogous to the result obtained by E. D. Livshitz [15] using dictionaries.